Patient Preferences and Treatment Thresholds under Diagnostic Risk – An Economic Laboratory Experiment - Miriam Krieger; Thomas Mayrhofer (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2012)
We study risk aversion and prudence in medical treatment decisions. In a laboratory experiment, we investigate the frequency and intensity of second- and third-order risk preferences, as well as the effect of the medical decision context. Risk preferences are assessed through treatment thresholds (the indifference point between not treating and treating). Under diagnostic risk, medical decision theory predicts lower thresholds for risk-averse than risk-neutral decision makers. Given a comorbidity risk, prudent individuals have an even lower threshold. Our results demonstrate risk-averse and prudent behavior in medical decisions, which reduce the (average) treatment threshold by 41% relative to risk neutrality (from 50.0% to 29.3% prevalence rate). Risk aversion accounts for 3/4 of this effect, prudence for 1/4. The medical decision framing does not affect risk aversion, but is associated with more and stronger prudent behavior. These findings have consequences for treatment thresholds, diagnostics, and QALYs, and thus for clinical guidelines. – – Wir untersuchen mittels eines Laborexperiments den Einfluss von Risikoscheue und Vorsicht (Prudence) auf medizinische Behandlungsentscheidungen. Neben der Häufigkeit und Intensität von Risikopräferenzen zweiter und dritter Ordnung untersuchen wir auch den Effekt des medizinischen Entscheidungskontextes. Wir ermitteln die Risikopräferenzen über Behandlungsschwellenwerte (Indifferenzpunkte zwischen nicht behandeln und behandeln). Unter diagnostischem Risiko sollte laut der medizinischen Entscheidungstheorie der Behandlungsschwellenwert für risikoscheue Entscheider kleiner sein als für risikoneutrale Entscheider. Tritt zusätzlich ein Komorbiditätsrisiko auf, senken vorsichtige Entscheider ihren Schwellenwert noch weiter ab. Unsere Ergebnisse lassen auf risikoscheues und vorsichtiges Verhalten schließen: Probanden wählen ihren Behandlungsschwellenwert im Durchschnitt 41% unterhalb des risikoneutralen Schwellenwertes (Verschiebung von 50% auf 29,3% Prävalenz). Risikoaversion ist für dieses Effekts, Vorsicht für verantwortlich. Das medizinische Framing hat keinen Einfluss auf Risikoscheue, bewirkt jedoch häufigeres und stärkeres vorsichtiges Verhalten. Unsere Ergebnisse haben Konsequenzen für Behandlungsschwellenwerte, diagnostische Tests sowie QALYS und damit medizinische Leitlinien.
Keywords: I10; C91; D81; 330; Medical decision making; treatment thresholds; risk aversion; prudence; laboratory experiment